ISLAMIC VALUES ON â€œAJARI AKU ISLAMâ€ MOVIE (ISLAMIC LITERATURE) - Tawvicky Hidayat (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
AbstractThis article reveals Islamic Â values in â€œAjari Aku Islamâ€ Film. The core of the article is to explain the philosophical values of the film on the perspective of love and life values. The main analysis of this article is using Islamic Perspectives, therefore it will be found some analysis using alquran and hadits in this research. It is found in this article that Â the movie Ajari Aku Islam contains many Islamic Â messages that have categories namely establishing prayer, forbidden to touch with non-muhrim, keeping the gaze and covering the aurat, studying the religion of islam, good manner, forgive to allah, help each other, friendly to everyone.Keywords: Islamic Â values, Ajari Aku Islam. The core of life, the core of loveAbstrakArtikel ini mengungkapkan nilai-nilai Islam dalam film